Optimierung expositionsbasierter Therapie: Ein Ansatz des inhibitorischen Lernens - Pittig, Andre; Stevens, Stephan; Vervliet, Bram; Treanor, Michael; Conway, Christopher C.; Zbozinek, Tomislav; Craske, Michelle G. (Psychotherapeut, 2015)
Exposure is an effective approach for treating anxiety disorders, although a substantial number of individuals fail to benefit or experience a return of fear. Research results suggest that anxious individuals show deficits in the mechanisms underlying exposure therapy, such as inhibitory learning. Targeting these processes may help improve the efficacy of exposure; however, there has been little discussion of how to implement this model in clinical practice. The primary aim of this paper is to provide examples to clinicians for how to apply this model to optimize exposure therapy, in ways that distinguish it from a fear habituation approach and a belief disconfirmation approach. Optimization strategies include (1) expectancy violation, (2) deepened extinction, (3) occasional reinforced extinction, (4) removal of safety signals, (5) variability, (6) retrieval cues, (7) multiple contexts and (8) affect labeling. Case studies illustrate methods of applying these techniques with a variety of anxiety disorders.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Anxiety disorders; Case studies; Clinical application; Exposure therapy; Extinction